'The price is different depending on whether you want a receipt or not': examining the purchasing of goods and services from the informal economy in South-East Europe. Issue 11 (10th September 2018) - Littlewood, David; Rodgers, Peter; Yang, Junhong
ABSTRACT: Research on the informal economy has largely focussed on supply-side issues, addressing questions like what motivates individuals to work in the informal economy and how can governments tackle this phenomenon. To date, much less attention has been given to demand-side aspects, examining issues around who purchases goods and services from the informal economy, why, and to what extent there are variations according to demographic, socio-economic and geographic dimensions. This paper addresses this imbalance by examining the purchasing of goods and services from the informal economy in South-East Europe. Firstly, this paper identifies the prevalence of such informal purchasing in South-East Europe as well as who undertakes such purchasing. Next, it examines the relative significance of cost factors, social factors and failures in the formal economy, in motivating such purchasing. Finally, it explores variability in the significance of these motivators based on individual-level factors, within and across three South-East European countries.